2019
DOI: 10.1111/ejn.14536
|View full text |Cite
|
Sign up to set email alerts
|

The ventrolateral periaqueductal grey updates fear via positive prediction error

Abstract: Aversive, positive prediction error (+PE) provides a mechanism to update and increase future fear to uncertain threat predictors. The ventrolateral periaqueductal grey (vlPAG) has been offered as a neural locus for +PE computation. Yet, a causal demonstration of vlPAG +PE activity to update fear remains elusive. We devised a fear discrimination procedure in which a danger cue predicts shock deterministically and an uncertainty cue predicts shock probabilistically, requiring prediction errors to achieve an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 36 publications
6
41
1
Order By: Relevance
“…Furthermore, to evaluate whether the state of the FN-vlPAG projections regulates the fear learning at the time of the CS-US association 37, 38 , we optogenetically stimulated the FN during the CS-US presentation (from the last 3 s of the CS until 3 s post CS-US, Fig.7 a, b, d). We found that mice exposed to the light stimulation exhibited a significant enhanced extinction of the fear response during the extinction sessions compared to the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to evaluate whether the state of the FN-vlPAG projections regulates the fear learning at the time of the CS-US association 37, 38 , we optogenetically stimulated the FN during the CS-US presentation (from the last 3 s of the CS until 3 s post CS-US, Fig.7 a, b, d). We found that mice exposed to the light stimulation exhibited a significant enhanced extinction of the fear response during the extinction sessions compared to the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the optogenetic inhibition of vlPAG has been found to inhibit the acquisition of conditioned fear response not only using aversive shocks but also using threatening visual stimuli 37 , thus, pointing to a broad role of the vlPAG in fear learning. Indeed, a number of electrophysiological recordings and optogenetic manipulations indicate that vlPAG neurons encode positive fear prediction errors which determine the intensity of fear learning 38, 4143 .…”
Section: Discussionmentioning
confidence: 99%
“…This is based on our observation that female rats readily acquire fear discrimination 37 . Further, manipulating shock-related prediction error activity -although a distinct behavioural mechanism from facilitationhas an equivalent effect on male and female fear behaviour 34 . We speculate that facilitation -like fear discrimination and prediction error -is a behavioural mechanism conserved across sexes.…”
Section: Discussionmentioning
confidence: 96%
“…So far, no differences in VP activity/function have been found in studies that examined biological sex 18,39,55 . Our laboratory has observed complete and comparable fear discrimination in male and female rats 11,51,56,57 . We predict that equivalent relative threat signaling will be observed in female and male VP neurons.…”
Section: Cue-excited Neurons Increase Firing To Rewardmentioning
confidence: 89%